2016
DOI: 10.1093/gbe/evw147
|View full text |Cite
|
Sign up to set email alerts
|

Assembled Plastid and Mitochondrial Genomes, as well as Nuclear Genes, Place the Parasite Family Cynomoriaceae in the Saxifragales

Abstract: Cynomoriaceae, one of the last unplaced families of flowering plants, comprise one or two species or subspecies of root parasites that occur from the Mediterranean to the Gobi Desert. Using Illumina sequencing, we assembled the mitochondrial and plastid genomes as well as some nuclear genes of a Cynomorium specimen from Italy. Selected genes were also obtained by Sanger sequencing from individuals collected in China and Iran, resulting in matrices of 33 mitochondrial, 6 nuclear, and 14 plastid genes and rDNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 53 publications
7
69
0
Order By: Relevance
“…The hypothesis of increased HGT frequency in endoparasites compared with exoparasites was proposed in studies of HGT in the parasitic plants Rafflesia (20,25) and Cynomorium (22). Our study revealed increased numbers of HGT among related species with increased heterotrophic dependence, a pattern that could be corroborated with rigorous HGT identification in a much larger sampling of parasitic taxa from Orobanchaceae and other parasitic lineages (65) of varying ages and degrees of nutritional dependence.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The hypothesis of increased HGT frequency in endoparasites compared with exoparasites was proposed in studies of HGT in the parasitic plants Rafflesia (20,25) and Cynomorium (22). Our study revealed increased numbers of HGT among related species with increased heterotrophic dependence, a pattern that could be corroborated with rigorous HGT identification in a much larger sampling of parasitic taxa from Orobanchaceae and other parasitic lineages (65) of varying ages and degrees of nutritional dependence.…”
Section: Resultssupporting
confidence: 81%
“…A second apparent concentration of horizontally acquired sequences in plant genomes is associated with parasitic plants, where both mitochondrial (14,(17)(18)(19)(20)(21)(22)(23) and nuclear horizontal transfers (24)(25)(26)(27)(28)(29) have been identified. Repeated horizontal acquisitions of mitochondrial atpI by parasitic flowering plants occurred in four extreme parasite lineages where the parasite lives inside the host for much of its lifespan (14).…”
Section: Significancementioning
confidence: 99%
“…Plastomes in the holoparasitic species of Orobanchaceae are also heavily degraded2391011, most extensively in Conopholis americana whose plastome is only 46 kb in size with just 21 intact protein-coding genes. Similar levels of degradation were found in the plastomes of other holoparasites in Cynomoriaceae and Hydnoraceae1213. Even greater genomic reduction was reported in Pilostyles (Apodanthaceae), whose plastomes are reduced to just 11–15 kb and may contain only five or six functional genes14.…”
supporting
confidence: 56%
“…In addition to the Orobanchaceae data reported here, large-scale mitogenomic data from a parasitic plant is available from four hemiparasitic mistletoes1617, four holoparasitic members of Rafflesiaceae1537, and a holoparasite in Cynomoriaceae13. As in the Orobanchaceae parasites described here, the Cynomoriaceae and Rafflesiaceae holoparasites contain a nearly complete set of the expected mitochondrial genes, although a substantial fraction were reported to have been acquired horizontally1337.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation